Risk factors of methicillin-resistant Staphylococcus aureus colonization in the nasal cavity of people living with HIV: a cross-sectional study from Dongyang hospital, Zhejiang Province - Hu, Dongping; Hong, Li; Ye, Tinghua; Yang, Bin; Wang, Lixia (Frontiers in Microbiology, 2025)
ObjectiveTo investigate the distribution characteristics of methicillin-resistant Staphylococcus aureus (MRSA) infection in people living with HIV (PLWH), to analyse the risk factors of MRSA colonisation in the nasopharynx of PLWH, and to provide a scientific basis for the prevention of hospital-acquired MRSA infection in PLWH.MethodsThis study used a cross-sectional research design to analyse 1,100 PLWH attending the AIDS outpatient clinic of the People’s Hospital of Dongyang City, Zhejiang Province, from January 2022 to December 2024. Nasal swabs were collected with informed consent, and epidemiological information was collected via questionnaire. Standard microbiological methods were used for isolation and identification of strains, with drug susceptibility testing performed using the K-B paper diffusion method. PCR was used to detect virulence genes pvl and tst. Statistical analysis was conducted using Stata13.0 software.ResultsOf the 1,100 PLWH enrolled, 275 (25%) were colonized with S. aureus, of which 98 (35.63%) carried MRSA and 177 (64.37%) carried MSSA. The mean age of MRSA carriers (51.32 ± 15.87 years) was significantly higher than that of MSSA carriers (44.26 ± 18.93 years) (p < 0.001). MRSA had a high prevalence of resistance to a wide range of antibiotics, including penicillin, oxacillin, amoxicillin and amoxicillin/clavulanic acid. The virulence gene pvl was detected more frequently in MSSA than in MRSA. In PLWH, respiratory infections in the previous 12 months, lack of antiretroviral therapy and heterosexual transmission were associated with a higher risk of nasal carriage of MRSA.ConclusionThe study provides valuable insights into the characteristics and distribution of MRSA and MSSA cases, as well as the factors influencing the nasal carriage of Staphylococcus aureus, particularly MRSA, in PLWH. These findings can guide clinical practice and infection control measures to reduce the incidence and spread of MRSA infections in high-risk populations.